SUNDANESE AND JAVANESE: SUNDANESE NOBLEMEN POINT OF VIEW TOWARDS BUDI UTOMO - Mulyana, Agus (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2009)
Nationalism was born as a result of the education of colonial government in the early of the twentieth century. At the beginning, nationalism was based on the local or ethnic identities that gave birth to ethnonationalism. This ethno-nationalist point of view caused debates among Sundanese noblemen in responding to the establishment of Budi Utomo branch in Bandung.